Reasoned opinion on the modification of the existing MRLs for difenoconazole in peppers and aubergines. (29th April 2014) - ,
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, Greece, hereafter referred to as the evaluating Member State (EMS), received an application from SYGENTA HELLAS ABEE to modify the existing MRLs for the active substance difenoconazole in peppers and aubergines. In order to accommodate the intended uses of difenoconazole Greece proposed to raise the existing MRLs from the values of 0.5 mg/kg to 0.7 mg/kg for peppers and from 0.4 mg/kg to 0.6 mg/kg for aubergines. Greece drafted an evaluation report in accordance with Article 8 of Regulation (EC) No 396/2005, which was submitted to the European Commission and forwarded to EFSA. According to EFSA the data are sufficient to derive MRL proposals of 0.8 mg/kg for the proposed use on peppers and 0.4 mg/kg for the use on aubergines reflecting the indoor use. An alternative MRL proposal of 0.6 mg/kg was derived for aubergines for further risk management considerations, based on SEU outdoor trials which were performed with a higher number of applications compared to the notified GAP. Based on the risk assessment results, EFSA concludes that the proposed use of difenoconazole on peppers and aubergines will not result in a consumer exposure exceeding the toxicological reference values and therefore is unlikely to pose a consumer health risk. The risk assessment for the triazole derivative metabolites is still pending.